The demand of urban residents for the biodiversity conservation in U Minh Thuong National Park, Vietnam - Huynh Khai; Mitsuyasu Yabe (Agricultural and Food Economics, 2014)
The total economic value of biodiversity provides policy-makers reliable information to estimate welfare losses caused by biodiversity reductions and perform cost-benefit analysis of biodiversity conservation projects. Searching literature reviews on economic-valuation techniques, the contingent valuation (CV) method has been popularly applied to estimate the economic value of biodiversity. This approach is based on a hypothetical scenario in which respondents are requested through questionnaires to reveal their maximum willingness to pay (WTP) for biodiversity conservation. The article used CV to study the Mekong Delta urban households' preferences and their willingness to pay for the program of biodiversity conservation in U Minh Thuong National Park, one of the largest peat swamp forests in Vietnam. Logistic regression was used to predict the probability of respondents willing to pay for the conservation program. The mean WTP was calculated approximately VND16,510 (0.78) per household per month for all respondents and about VND31,520 (1.49) after excluding the protest zero and scenario rejecting respondents. Aggregately, Mekong Delta urban residents agreed to contribute about 10.97 million annually for the project of biodiversity conservation.
Keywords: 330; Contingent valuation; Genetic resources; Wetland conservation; WTP